Identification of cyst nematode B-type CLE peptides and modulation of the vascular stem cell pathway for feeding cell formation. - Xiaoli Guo; Jianying Wang; Michael Gardner; Hiroo Fukuda; Yuki Kondo; J Peter Etchells; Xiaohong Wang; Melissa Goellner Mitchum (PLoS Pathogens)
Stem cell pools in the SAM (shoot apical meristem), RAM (root apical meristem) and vascular procambium/cambium are regulated by CLE-receptor kinase-WOX signaling modules. Previous data showed that cyst nematode CLE-like effector proteins delivered into host cells through a stylet, act as ligand mimics of plant A-type CLE peptides and are pivotal for successful parasitism. Here we report the identification of a new class of CLE peptides from cyst nematodes with functional similarity to the B-type CLE peptide TDIF (tracheary element differentiation inhibitory factor) encoded by the CLE41 and CLE44 genes in Arabidopsis. We further demonstrate that the TDIF-TDR (TDIF receptor)-WOX4 pathway, which promotes procambial meristem cell proliferation, is involved in beet cyst nematode Heterodera schachtii parasitism. We observed activation of the TDIF pathway in developing feeding sites, reduced nematode infection in cle41 and tdr-1 wox4-1 mutants, and compromised syncytium size in cle41, tdr-1, wox4-1 and tdr-1 wox4-1 mutants. By qRT-PCR and promoter:GUS analyses, we showed that the expression of WOX4 is decreased in a clv1-101 clv2-101 rpk2-5 mutant, suggesting that WOX4 is a potential downstream target of nematode CLEs. Exogenous treatment with both nematode A-type and B-type CLE peptides induced massive cell proliferation in wild type roots, suggesting that the two types of CLEs may regulate cell proliferation during feeding site formation. These findings highlight an important role of the procambial cell proliferation pathway in cyst nematode feeding site formation.